A retrospective description of anesthetic medication dosing in overweight and obese children. Issue 8 (8th April 2014) - Burke, Constance N.; Voepel‐Lewis, Terri; Wagner, Deborah; Lau, Irwin; Baldock, Andrew; Malviya, Shobha; Nafiu, Olubukola; Lerman, Jerrold
Summary Introduction Pediatric obesity is a major health concern in the United States and as many as 34% of those who require general anesthesia are overweight or obese (OW). The lack of data and recommendations for dosing medications in obese children leaves significant gaps in the understanding of correct dosing in the clinical setting. Objective To determine whether OW children were more likely to receive doses of medications outside the recommended range. Methods Following IRB approval, patient medical records were queried to identify children 2 through 17 years who underwent noncardiac surgeries and received at least one medication of interest. Children with hepatic disease, renal disease, neurological impairment, sleep‐disordered breathing, or missing height or weight measurements were excluded. Children were stratified into weight categories based on age and gender percentiles as per CDC guidelines. Those ≥85th percentile were classified as overweight/obese. Ideal and lean weight (for age, gender) were calculated. Drug doses were stratified as under‐dosed (>10% below minimum recommended dose), overdosed (>10% above maximum recommended dose), or within recommended dose (dose ± 10%). Actual doses were compared to recommended doses as per actual, ideal, or lean weight (as recommended for specific drugs) in the overweight/obese groups vs the control weight (CW) group. Results Ten thousand five hundred and nine doses were reviewed. Overweight/obese children were more likely to receive doses outside the recommended dose range than the CW group. Conclusions Overweight/obese children were more likely to receive doses of common anesthetic medications outside the recommended doses potentially adding risk of adverse outcomes in these children.